NATIONALISTIC CONSCIOUSNESS AND GANDHIAN PRINCIPALS IN THE NOVELS OF BHABANI BHATTACHARYA - Dr. Sunil Garg (Innovative Research Thoughts, 2023)
Nationalism is a weapon for a dominated community to fight with the foreign rule of an imperialist country. The concept of Nationalism was born in the eighteenth century during the French Revolution in the European continent as adoration of collective power. India was a conglomeration of diverse states and principalities where there lived various peoples of different races and religions, castes and sub castes speaking a number of languages and dialects. By 1875, the seeds of nationalism sown by the British rule itself had germinated in the soil of India, and the erstwhile geographical term had acquired a new meaning and a new significance. The main Indian Freedom struggle began under the leadership of M.K. Gandhi. Gandhi and his followers also wanted Purna Swaraj or complete freedom from British rule through non-violent passive resistance like Tilak and others of the earlier phase. The two phases are not very distinct from each other and can be treated as one. Gandhi differed from Tilak in the sense that he insisted more on moral elevation of the people of India for winning freedom than Tilak had done. Non-violence was Gandhi‘s weapon for winning freedom as it was for the earlier leaders. But to it, he added a new meaning and a new significance. He philosophized and idealized these and other allied terms to the farthest possible extent. Bhabani Bhattacharya is one of the Indo-Anglian novelists and short story writers of the period who were witness to dramatic events of the period and had felt the spirit of those times in their own veins have depicted these movements in their writings.